2019
DOI: 10.1002/ps.5538
|View full text |Cite
|
Sign up to set email alerts
|

Origin of resistance to pyrethroids in the redlegged earth mite (Halotydeus destructor) in Australia: repeated local evolution and migration

Abstract: BACKGROUND: Halotydeus destructor is a major pest of crops and pastures across southern parts of Australia. This invasive mite has been chemically controlled for over 50 years, but resistance to synthetic pyrethroids and organophosphates is developing. Understanding processes behind the emerging resistance is important for effective management efforts. We undertook a ddRAD pool-sequencing approach to analyse genome-wide single nucleotide polymorphism variation in H. destructor population samples at two scales:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 38 publications
2
55
2
Order By: Relevance
“…While the role of human transportation in establishing geographical distributions of Aedes mosquitoes is already well recognised (Tatem, Hay, & Rogers, 2006), these results indicate that dispersal along transportation networks has also helped to establish current distributions of pyrethroid resistance mutations. These results stand in contrast to a similar investigation of pyrethroid resistance in Australian red‐legged earth mite ( Halotydeus destructor ) populations, which showed that the present distribution of resistance had been attained by multiple de novo mutations (Yang et al., 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While the role of human transportation in establishing geographical distributions of Aedes mosquitoes is already well recognised (Tatem, Hay, & Rogers, 2006), these results indicate that dispersal along transportation networks has also helped to establish current distributions of pyrethroid resistance mutations. These results stand in contrast to a similar investigation of pyrethroid resistance in Australian red‐legged earth mite ( Halotydeus destructor ) populations, which showed that the present distribution of resistance had been attained by multiple de novo mutations (Yang et al., 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…This in turn will depend on whether the incursive populations carry pesticide resistance alleles, which can arise through in situ evolution of resistance alleles and/or through the introduction of resistance alleles from other established populations. Both processes can be important in pest and disease vector control: examples of local evolution of resistance include pyrethroid resistance in the earth mite Halotydeus destructor (Yang et al., 2020) and organophosphate resistance in the whitefly Bemisia tabaci (Gauthier et al, 2014), whereas the long distance introduction of resistance genes is typified by pyrethroid resistance in the mosquito Culex pipiens (Chevillon, Raymond, Guillemaud, Lenormand, & Pasteur, 1999); the contribution of both these factors in invading populations is highlighted by pesticide resistance in the spider mite Tetranychus urticae (Shi et al., 2019) and the moth Spodoptera frugiperda (Nagoshi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results stand in contrast to a similar investigation of pyrethroid resistance in Australian red-legged earth mite (Halotydeus destructor) populations, which showed that the present distribution of resistance had been attained by multiple de novo mutations (Yang et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…To resolve the importance of local mutation/selection and the movement of resistance alleles between populations, the distribution of resistant alleles can be compared to high resolution patterns of genetic differentiation among populations (Yang et al, 2019). Genomic approaches using single nucleotide polymorphism (SNP) markers have been highly effective at identifying differentiation among Ae.…”
Section: Introductionmentioning
confidence: 99%